Afectividad en los hijos frente a las nuevas relaciones parentales. - Espinoza Chunzho, Carmen Alexanadra (2015)
This research work has as its general objective to describe the affective manifestations of children against new parental relationships in response to the reconstruction of the family after a divorce, under the guidelines of integrative model which unifies theoretical constructs for understanding the human being in its whole.